Aorta calcification burden: Towards an integrative predictor of cardiac outcome after transcatheter aortic valve implantation. (March 2016) - Harbaoui, Brahim; Montoy, Mathieu; Charles, Paul; Boussel, Loic; Liebgott, Hervé; Girerd, Nicolas; Courand, Pierre-Yves; Lantelme, Pierre
Abstract: Objective: The principal objective was to determine the effect of total aortic calcification (TAC) burden on outcomes (cardiac mortality, all-cause mortality, and heart failure (HF)) after transcatheter aortic valve implantation (TAVI). The secondary aim was to assess the contribution of each segment of the aorta to these outcomes. Background: Indications for TAVI are increasing in number. Even after procedural success, however, some patients die soon afterwards, indicating the futility of TAVI in certain cases. Methods: Aortic calcifications were measured on computed tomography in 164 patients treated by TAVI. TAC, ascending aortic calcification (AsAC), descending aorta calcifications, and abdominal aorta calcifications were expressed as tertiles and their prognostic values were assessed in a multivariable cox analysis adjusted for major confounders including EuroSCORE. Results: Median duration of follow-up was 565 (interquartile range: 246 to 1000) days. TAC (tertile3 vs. tertile1) was significantly and strongly associated with cardiac mortality (hazard ratio [HR]: 16.74; 95% confidence interval [CI]: 2.21 to 127.05; p = 0.006) and all-cause mortality (HR: 2.39; 95% CI: 1.18 to 4.84; p = 0.015) but not with HF (HR: 1.84; 95% CI: 0.87 to 3.90; p = 0.110). Each segment was associated with cardiac mortality, while only AsAC (tertile 3 vs. tertile 1) appeared predictive of HF (hazard ratio: 2.29; 95% CI: 1.12 to 4.66; p = 0.023). Conclusions: TAC is an integrative predictor of cardiac and all-cause mortality after TAVI. It should be included in the assessment of patients before TAVI in order to predict cardiac outcome after valve replacement and avoid futile interventions. Highlights: We studied associations of aortic calcifications and outcomes after TAVI. Total aortic calcifications predicted cardiac mortality and all-cause mortality. Calcifications of all aorta segments predicted cardiac mortality. Only Ascending aorta calcifications predicted heart failure. Assessing aortic calcifications should be considered for risk stratification before TAVI.